PEMANFAATAN MEDIA SOSIAL DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI): STUDI PARTICIPATORY ACTION RESEARCH PADA SISWA KELAS X MAN 1 KOTA PALANGKA RAYA - olivia; Suryanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article presents findings from participatory action research (PAR) aimed at exploring and implementing the use of social media in Islamic Cultural History (IS) learning in Grade 10E of MAN 1 Palangka Raya City. Amidst the dominance of the digital era and the challenges of conventional IS learning in attracting students' interest, this research seeks to transform Islamic historical narratives into dynamic and relevant content through digital platforms familiar to adolescents. The PAR approach was chosen to ensure active collaboration between researchers and students, empowering them as agents in the learning process. The research cycle, which included planning, action, observation, and reflection, focused on developing participatory IS learning strategies based on social media. Through data analysis from questionnaires, observations, social media content analysis, and interviews, it was found that the use of platforms such as Instagram, TikTok, and WhatsApp significantly increased student engagement with IS material. Students demonstrated higher enthusiasm, deeper understanding, and the development of crucial digital skills. Challenges related to access and distractions were overcome through collaboration and adaptation to the local context. This study concludes that social media, with the right strategies, is an effective tool for revitalizing SKI learning, empowering students to become independent, creative, and digitally literate learners. Recommendations are provided for schools, teachers, and students to continue integrating and optimally utilizing social media in SKI education.